Identifikasi Cendawan Patogen Penyebab Penyakit pada Daun Jabon Merah (Anthocephalus macrophyllus (Roxb.) Havil) - Elis Nina Herliyana; Liza Sakbani; Yeni Herdiyeni; Abdul Munif (Jurnal Silvikultur Tropika, 2020)
Red Jabon (Anthocephalus macrophyllus (Roxb.) Havil) is a forest plant that can replace sengon (Falcataria moluccana) because it has advantages. The demand for red jabon wood is increasing, but the cultivation of red jabon is still constrained by the attack of pathogens that cause leaf disease. The attack of these pathogens can cause damage and death of seedlings so that it can be economically detrimental. The aim of this study was to identify the pathogens that cause disease in red Jabon. The method used is the Postulate Koch method, which starts from sampling red leaves with leaf disease symptoms, isolation, inoculation and analysis of disease incidence, re-isolation, and identification. Based on the identification results found as many as 2 pathogenic fungi that cause leaf spot disease, namely Pestalotia sp. and Rhizoctonia sp. In addition, 6 pathogenic fungi were found that cause blight, namely Lasiodiplodia theobromae, Fusarium sp., Colletrotrichum sp., Marssonina sp., Gloeosporium sp. 1, Gloeosporium sp. 2. Keywords: identification, percentage of disease incidence, Postulat Koch, red jabon